Personalized Medicine Approaches in Prostate Cancer Employing Patient Derived 3D Organoids and Humanized Mice - Bartucci, Monica; Ferrari, Anna C.; Kim, Isaac Yi; Ploss, Alexander; Yarmush, Martin; Sabaawy, Hatem E. (Frontiers in Cell and Developmental Biology, 2016)
Prostate cancer (PCa) is the most common malignancy and the second most common cause of cancer death in Western men. Despite its prevalence, PCa has proven very difficult to propagate in vitro. PCa represents a complex organ-like multicellular structure maintained by the dynamic interaction of tumoral cells with parenchymal stroma, endothelial and immune cells and components of the extracellular matrix (ECM). The lack of PCa models that recapitulate this intricate system has hampered progress towards understanding disease progression and lackluster therapeutic responses. Tissue slices, monolayer cultures and genetically engineered mouse models (GEMM) fail to mimic the complexities of the PCa microenvironment or reproduce the diverse mechanisms of therapy resistance. Moreover, patient derived xenografts (PDXs) are expensive, time consuming, lack immune cell-tumor regulation and often tumors undergo selective engraftments. Here, we describe an interdisciplinary approach using primary PCa and tumor initiating cells (TICs), three-dimensional (3D) tissue engineering, genetic and morphometric profiling and humanized mice to generate patient-derived organoids for examining personalized therapeutic responses in vitro and in mice co-engrafted with a human immune system (HIS), employing adaptive T-cell- and chimeric antigen receptor- (CAR) immunotherapy. The development of patient specific therapies targeting the vulnerabilities of cancer, when combined with antiproliferative and immunotherapy approaches could help to achieve the full transformative power of cancer precision medicine.